Analysis of Entrepreneurship Learning in Higher Education: A Quantitative and Qualitative Study - Hestiningtyas, Widya; Herpratiwi, Herpratiwi; Maydiantoro, Albet (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study aims to evaluate the success rate of entrepreneurship education in higher education institutions through a mixed-methods approach, incorporating both quantitative and qualitative data. Data were collected via a Google Form questionnaire, completed by 282 respondents from various provinces, universities, and institutions. The respondents included students, lecturers, education practitioners, business owners, MSMEs, alumni, government agencies, and members of digital and media communities. The quantitative analysis indicated that while most respondents demonstrated a strong theoretical understanding of entrepreneurship, practical business implementation remained limited and represented a significant obstacle. Success factors identified included internal motivation, opportunities for field practice, and lecturer support, while barriers were largely attributed to limited capital and an overemphasis on theoretical learning. Qualitative findings highlighted the need for enhanced project-based learning, active collaboration with SMEs, digital marketing training, and the organization of bazaars that actively engage students. This study is limited by the relatively small sample size, the use of perception-based questionnaires, and the focus on entrepreneurship education in higher education within the context of the pentahelix model. Based on these findings, the study recommends strengthening the pentahelix-based entrepreneurship learning model, which promotes collaborative synergy between universities, government, industry, media, and the community to foster a more dynamic and sustainable entrepreneurial ecosystem.